Mapping low-resource contexts to prepare for lung health interventions in four countries (FRESH AIR): a mixed-method study - Evelyn A Brakema, MD; Rianne M J J van der Kleij, PhD; Charlotte C Poot, MSc; Pham Le An, MD; Marilena Anastasaki, MSc; Matty R Crone, PhD; Le Huynh Thi Cam Hong, MSc; Bruce Kirenga, PhD; Christos Lionis, ProfPhD; Maamed Mademilov, MD; Mattijs E Numans, ProfPhD; Lê Thi Tu Oanh, MSc; et al. (Elsevier, 2022)
Summary: Background: Effectiveness of health programmes can be undermined when the implementation misaligns with local beliefs and behaviours. To design context-driven implementation strategies, we explored beliefs and behaviours regarding chronic respiratory disease (CRD) in diverse low-resource settings. Methods: This observational mixed-method study was conducted in Africa (Uganda), Asia (Kyrgyzstan and Vietnam) and Europe (rural Greece and a Roma camp). We systematically mapped beliefs and behaviours using the SETTING-tool. Multiple qualitative methods among purposively selected community members, health-care professionals, and key informants were triangulated with a quantitative survey among a representative group of community members and health-care professionals. We used thematic analysis and descriptive statistics. Findings: We included qualitative data from 340 informants (77 interviews, 45 focus group discussions, 83 observations of community members' households and health-care professionals' consultations) and quantitative data from 1037 community members and 204 health-care professionals. We identified three key themes across the settings; namely, (1) perceived CRD identity (community members in all settings except the rural Greek strongly attributed long-lasting respiratory symptoms to infection, predominantly tuberculosis); (2) beliefs about causes (682 [65·8%] of 1037 community members strongly agreed that tobacco smoking causes symptoms, this number was 198 [19·1%] for household air pollution; typical perceived causes ranged from witchcraft [Uganda] to a hot-cold disbalance [Vietnam]); and (3) norms and social structures (eg, real men smoke [Kyrgyzstan and Vietnam]). Interpretation: When designing context-driven implementation strategies for CRD-related interventions across these global settings, three consistent themes should be addressed, each with common and context-specific beliefs and behaviours. Context-driven strategies can reduce the risk of implementation failure, thereby optimising resource use to benefit health outcomes. Funding: European Commission Horizon 2020. Translations: For the Greek, Russian and Vietnamese translations of the abstract see Supplementary Materials section.